Charge carrier trapping in highly-ordered lyotropic chromonic liquid crystal films based on ionic perylene diimide derivatives. Issue 3 (24th November 2014) - Soroka, Pavlo V.; Vakhnin, Alexander Yu.; Skryshevskiy, Yuriy A.; Boiko, Oleksandr P.; Anisimov, Maksim I.; Slominskiy, Yuriy L.; Nazarenko, Vassili G.; Genoe, Jan; Kadashchuk, Andrey
Abstract : Charge carrier trapping in thin films of lyotropic chromonic liquid crystals (LCLCs) based on ionic perylene diimide derivative and in chemically-similar neutral N, N′-dipentyl-3, 4, 9, 10-perylene-dicarboximide (PTCDI-C5) films is investigated by thermally-stimulated luminescence (TSL) technique. The LCLC films comprise elongated molecular aggregates featuring a long-range orientational order. The obtained results provide direct evidence for the improved energetic ordering (smaller effective energetic disorder) in aggregated LCLC films as compared to conventional PTCDI-C5 films. The width of the density-of-state distribution of 0.09 eV and 0.13 eV was estimated for the LCLC and PTCDI-C5 films, respectively. Relatively small effective energetic disorder in LCLC films is ascribed to formation of macroscopically larger LCLC aggregates.